2016
DOI: 10.7717/peerj.1855
|View full text |Cite
|
Sign up to set email alerts
|

Unique haplotypes of cacao trees as revealed bytrnH-psbAchloroplast DNA

Abstract: Cacao trees have been cultivated in Mesoamerica for at least 4,000 years. In this study, we analyzed sequence variation in the chloroplast DNA trnH-psbA intergenic spacer from 28 cacao trees from different farms in the Soconusco region in southern Mexico. Genetic relationships were established by two analysis approaches based on geographic origin (five populations) and genetic origin (based on a previous study). We identified six polymorphic sites, including five insertion/deletion (indels) types and one trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…High LD was characterized by many red squares in the heatmap generated. Many red blocks together would correspond to haplotype blocks [85,86].…”
Section: Tests Of Significance Of Associationmentioning
confidence: 99%
“…High LD was characterized by many red squares in the heatmap generated. Many red blocks together would correspond to haplotype blocks [85,86].…”
Section: Tests Of Significance Of Associationmentioning
confidence: 99%
“…La pequeña región nuclear escogida no representa todo el genoma y, por lo tanto, no cuenta toda la evolución genética de la especie. El análisis de marcadores de DNA de cloroplasto (cpDNA) se ha utilizado cada vez más en genética de poblacionales para determinar su estructura, ujo de genes, frecuencia de haplotipos y relaciones logenéticas (Gutiérrez-López et al, 2016). Por esta razón, se hizo una evaluación in silico de otros marcadores de secuencia del genoma de cloroplasto, que permitirán hacer en el futuro análisis más profundos y precisos entre cultivares de cacao.…”
Section: Análisis Genotípicounclassified
“…In addition to markers based on nuclear genomic DNA, several loci of chloroplast DNA (cpDNA) such as matK , rbcL and trnH‐psbA can be used as markers in DNA barcoding (Bieniek et al ., ). Recently, sequence variation of the trnH‐psbA intergenic spacer has been analysed in 28 cacao accession obtained from different farms in southern Mexico (Gutiérrez‐López et al ., ). It was found that the indels located in this region could be considered as potential markers for development of a DNA barcoding system in cacao.…”
Section: Introductionmentioning
confidence: 97%
“…It was found that the indels located in this region could be considered as potential markers for development of a DNA barcoding system in cacao. These markers are useful in identification of accessions in situations when other marker systems can only discriminate between accessions on the basis of a very small number of SSR markers (Gutiérrez‐López et al ., ).…”
Section: Introductionmentioning
confidence: 97%